2020
DOI: 10.1039/c9nj05834f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filler loading on polymer chain confinement and thermomechanical properties of epoxy/boron nitride (h-BN) nanocomposites

Abstract: This article examines the effect of the addition of hexagonal boron nitride (h-BN) nanopowder on the polymer chain confinement, thermal, morphological and mechanical properties of the epoxy system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…Owing to the highest flexibility, the unfilled vulcanizate exhibited the highest mechanical loss factor at T g (tan δ Tg of approximately 2.5). The addition of fillers decreased the height of the tan δ peak due to the reduction in the chains' mobility compared to the unfilled elastomer matrix [87]. As was concluded previously, based on the results of tensile properties, the applied fillers enhanced the stiffness and consequently reduced the flexibility of the NR vulcanizates and, therefore, the values of tan δ at T g .…”
Section: Nr Vulcanizates T G ( • C)supporting
confidence: 59%
“…Owing to the highest flexibility, the unfilled vulcanizate exhibited the highest mechanical loss factor at T g (tan δ Tg of approximately 2.5). The addition of fillers decreased the height of the tan δ peak due to the reduction in the chains' mobility compared to the unfilled elastomer matrix [87]. As was concluded previously, based on the results of tensile properties, the applied fillers enhanced the stiffness and consequently reduced the flexibility of the NR vulcanizates and, therefore, the values of tan δ at T g .…”
Section: Nr Vulcanizates T G ( • C)supporting
confidence: 59%
“…Mechanical properties of epoxy/h‐BN composites were effectively improved by the incorporation of 0.5 wt% h‐BN particles. [ 178 ] In another report by Chen et al, composites of epoxy fabricated using PVDF‐BN scaffolds showed significantly enhanced thermal conductivities compared with conventional epoxy/BN composites. [ 179 ] This type of epoxy‐based composite with high thermal conductivity can be identified as potential thermal management materials for advanced electronic devices.…”
Section: Polymer/boron Nitride Nanocomposites: Classificationsmentioning
confidence: 99%
“…In addition, it could be stated that the increase in the viscosity of adhesive after 3% reinforcement ratio was effective in decrease T g values. 29,46 According to the curing exotherms, ΔH curing values were decreased in reinforced adhesives compared with unreinforced adhesives. In this context, the heat capacity (C p ) were reduced up to 5% reinforcement ratio compared to neat adhesive and then these values with increasing nanoparticle ratio.…”
Section: Results Of Dscmentioning
confidence: 99%
“…When the derivatives of the thermograms are examined, the maximum degradation temperatures for the 2nd step were found to be around 375-390 C. Reinforcement does not appear to have any negative effect on the degredation rate. 46,47 In addition, with addition into epoxy, total weight loss reduced up to 2% fortification. Weight loss values are near in 1, 2, and 3% ratios.…”
Section: Results Of Tgamentioning
confidence: 99%